Computation of magnetic field from quadruple tower transmission lines in Malaysia - Said I.; Hussain H.B. (2023)
Public concern related to the adverse health effects of magnetic fields emanating from overhead power transmission lines resulted in a growing need to develop methods aimed at reducing such hazards. This paper presents the results of magnetic field simulation studies conducted on the quadruple tower transmission lines currently used in Malaysia. The results of the simulation studies were categorized to indicate the best conductor phase arrangement for lowest peak magnetic field, lowest average magnetic field and lowest magnetic field at the edge of the right-of-way. It was found that magnetic field reduction of more than 91.5% can be achieved using proper conductor phase arrangement.